Development of Mathematical Literacy Problems using East Kalimantan Context - Rusdiana, Rusdiana; Samsuddin, Auliaul Fitrah; Muhtadin, Achmad; Fendiyanto, Petrus (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2023)
A deep understanding of advanced mathematics is essential. This is without doubt. However, mathematics that is applicable on daily life is deemed more important. At least for the ones that does not belong to pure mathemacs field. One des not need to be a mathematics professor to be able to predict commute time to their work or to decide which clothes to buy with given amount of discount. This is also known as mathematical literacy. One of the key features of mathematical literacy is the integration of context. Developing or designing mathematical literacy task with local context is one of efforts to promote students’ mathematical literacy. This is because students are already familiar with the context hence they cam understand the problem statement better. The current study is design research aiming to develop mathematical literacy problems with East Kalimantan context. There are two phases in this research. The first phase is the preliminary phase. Here, PISA 2012 mathematics problems are reviewed and then researchers developed prototype problems with equal level but based on East Kalimantan context. There were nine mathematical literacy problems were developed in this phase. The second phase is the formative evaluation which consists of self evaluation, expert review and field test. From the process, nine valid items of problems with local context for measuring students’ mathematical literacy are obtained.